2017
DOI: 10.1186/s13071-017-2338-7
|View full text |Cite
|
Sign up to set email alerts
|

Natural antibody responses to Plasmodium falciparum MSP3 and GLURP(R0) antigens are associated with low parasite densities in malaria patients living in the Central Region of Ghana

Abstract: Background Plasmodium falciparum genetic diversity and multiplicity of infection (MOI) are parasite features that have been suggested to influence the acquisition of protective immunity against malaria. This study sought to assess the relationship between MOI and parasite density (PD) in malaria patients living in the Central Region of Ghana and to determine whether naturally occurring antibody levels against P. falciparum GLURP (PF3D7_1035300) and MSP3 (PF3D7_1035400) antigens are associated with decreased pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
5
14
2
1
Order By: Relevance
“…To determine if the Dd2 and W2mef cultures were contaminated with 3D7 or another SA-independent parasite strain, we sought to confirm the genetic identities of both Static and Suspended cultures of all three strains. Using the highly polymorphic merozoites surface protein 2 (MSP2) and previously described procedures 33 – 35 we confirmed that Suspended cultures of Dd2, W2mef and 3D7, were genetically identical to their respective Static cultures (Supplementary Figure S1 ). Furthermore, we found that erythrocyte surface expression levels of SA and CR1 were not significantly altered due to shaking (Supplementary Figure S2a and b ).…”
Section: Resultssupporting
confidence: 66%
“…To determine if the Dd2 and W2mef cultures were contaminated with 3D7 or another SA-independent parasite strain, we sought to confirm the genetic identities of both Static and Suspended cultures of all three strains. Using the highly polymorphic merozoites surface protein 2 (MSP2) and previously described procedures 33 – 35 we confirmed that Suspended cultures of Dd2, W2mef and 3D7, were genetically identical to their respective Static cultures (Supplementary Figure S1 ). Furthermore, we found that erythrocyte surface expression levels of SA and CR1 were not significantly altered due to shaking (Supplementary Figure S2a and b ).…”
Section: Resultssupporting
confidence: 66%
“…Total genomic DNA (gDNA) was extracted from the dried blood spot (DBS) using the Chelex extraction procedure [ 40 , 41 ]. Briefly, two 3 mm discs were punched out from the dried blood spots into 1.5 mL microcentrifuge tubes containing 1 mL of 1X phosphate buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Antibody responses including IgG, IgM, IgG1, and IgG3 against recombinant P. falciparum sexual stage and asexual stage antigens were quantified using an indirect ELISA protocol [41]. The antigens used in this study include Pfs230 [14] and MSP3 [30] produced in Lactococcus lactis. Briefly Pfs230 antigen was diluted to 1 µg/ ml in carbonate buffer [14,15] and MSP3 diluted to 1 µg/ ml in phosphate-buffered saline (1X PBS, pH7.2) [15,30] and 100 µl/well of the diluted antigen was used to coat the wells of Maxisorp NUNC plates (Nunc Maxisorp, UK) overnight at 4 °C.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…The antigens used in this study include Pfs230 [14] and MSP3 [30] produced in Lactococcus lactis. Briefly Pfs230 antigen was diluted to 1 µg/ ml in carbonate buffer [14,15] and MSP3 diluted to 1 µg/ ml in phosphate-buffered saline (1X PBS, pH7.2) [15,30] and 100 µl/well of the diluted antigen was used to coat the wells of Maxisorp NUNC plates (Nunc Maxisorp, UK) overnight at 4 °C. The plates were subsequently washed with wash buffer (PBST; 1X PBS supplemented with 0.05% Tween 20 at pH7.2), blocked with 3% nonfat skimmed milk (Marvel, UK) in1X PBS and incubated at room temperature (RT) for 1 h. The plates were then incubated with 100 µl/well of plasma diluted to 1:200 for IgG and IgM and 1:100 for IgG1 and IgG3 in 1% of non-fat skimmed milk in 1X PBS.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
See 1 more Smart Citation